Recognition of medical treatment rights in Thammasat University Hospital of students of Thammasat University - Wanpetch, Naritaya (Thammasat University Hospital Journal Online, 2025)
Background: Thammasat University has implemented a health insurance program for students in collaboration with Thammasat University Hospital to provide medical services and publicize information on the rights of medical treatment. Some students were unaware of their medical rights, procedures, and documentarys to receive medical services according to their medical treatment rights. Consequently, problems with receiving medical services arise. Objective: To study the perception of information on medical rights of Thammasat University students receiving services at Thammasat University Hospital. Materials and methods: This was an exploratory and descriptive study. Data were collected from 262 students from 17 faculties at Thammasat University, Rangsit Campus. Data were collected using a questionnaire on the perceptions of the right to receive medical treatment among students at Thammasat University Hospital. All data were analyzed using descriptive statistics, including frequencies and percentages. Results: 52.7% of students were aware of their rights to medical treatment, and 47.3% were unaware. Of the respondents, 66.3% were aware of all rights regarding medical treatment, while 34.3% were unaware. A total of 56.9% were aware of the procedures for exercising their rights. However, 43.1% were unaware of the procedures. 47.3%, 46.6 %, and 40.5 % of the students were aware of the documents/evidence to use for medical treatment at the hospital in case of sickness rights, accident rights, and universal health insurance patentability (gold card), respectively, while 59.5%, 53.4%52.0%, respectively, were unaware. In the case of publicizing the process of using medical treatment, 64.3% of the students received information about their rights to medical treatment from their peers, and 57% received information about their rights to medical treatment from Thammasat University's website. A total of 64% of students wanted to increase public relations channels on the Thammasat University website. Conclusion: Not more than 60.0% of the Thammasat University students on the Rangsit campus recognize their rights to medical treatment, procedures for exercising their rights, documents, and evidence for all medical treatment rights. They would like to receive information and treatment channels from the Thammasat University website.